2016
DOI: 10.1038/nature17647
|View full text |Cite
|
Sign up to set email alerts
|

The eyes of Tullimonstrum reveal a vertebrate affinity

Abstract: *Corresponding authorswith Tullimonstrum being a notable anomaly in this respect. Tullimonstrum, a monotypic taxon known from several hundred specimens, is preserved as stains with some relief within Mazon Creek siderite nodules. Despite the uncertainty about its position in the tree of life, there is a surprisingly high level of agreement regarding the arrangement and shape of anatomical features ( Fig.1 and Table. 1). The anatomical complexity, evident cardinal axes and the bilateral symmetry demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 23 publications
2
71
0
Order By: Relevance
“…Pigments also occur in association with light-sensing organs in invertebrate chordates, but we can reject the hypothesis that the pigmented structures in Myxinikela and Mayomyzon are similar to the light-detecting ‘eye’ of non-vertebrate chordates because they are paired, comparatively large and comprise a mass of melanosomes of dual morphology characteristic of vertebrates [8]. Mayomyzon also preserves evidence of a lens.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Pigments also occur in association with light-sensing organs in invertebrate chordates, but we can reject the hypothesis that the pigmented structures in Myxinikela and Mayomyzon are similar to the light-detecting ‘eye’ of non-vertebrate chordates because they are paired, comparatively large and comprise a mass of melanosomes of dual morphology characteristic of vertebrates [8]. Mayomyzon also preserves evidence of a lens.…”
Section: Discussionmentioning
confidence: 76%
“…This is the configuration of melanosomes in the vertebrate retinal pigmented epithelium (RPE): more cylindrically shaped melanosomes occur in the apical part, and melanosomes of oblate shape in the basal layer (see below). An identical arrangement of microbodies to those in Mayomyzon occurs in the eyes of osteichthyan fish taxa from the Mazon Creek, including Elonichthys peltigerus , Platysomus circularis and Esconicthys apopyris [8]. In other Lagerstätte, heterogeneous microbodies confined to fossil fish eyes are also interpreted as melanosomes of the RPE [12,13,21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a reanalysis of the character matrix fromMcCoy et al (2016) with some characters rescored,Sallan et al (2017) suggest that a non-vertebrate assignment for Tullimonstrum is more likely. Notwithstanding the uncertainty in its phylogenetic placement among stem lampreys, Tullimonstrum possesses a single long and low dorsal fin, as well as an asymmetrical oblanceolate caudal fin(Clements et al, 2016;McCoy et al, 2016).The interrelationships among lampreys, hagfishes and gnathostomes have been debated for many years, and two competing hypotheses have been proposed: (1) either lampreys and hagfishes form a clade called the cyclostomes(Duméril, 1806;Schaeffer & Thomson, 1980;Shimeld & Donoghue, 2012), (2) or hagfishes are craniates while lampreys are vertebrates, making the 'cyclos-…”
mentioning
confidence: 99%
“…Using electron microscopy and ToF-SIMS, the team identified melanosomes in the creature's eyes, arranged in layers typical of vertebrates. The team concluded that the Tully monster was a vertebrate, albeit an unusual one (13).…”
Section: From Color To Behaviormentioning
confidence: 99%